Evaluating in vitro antioxidant activity and GC-MS analysis of Scoparia dulcis Linn (Scrophulariacae) - Wankupar Wankhar, Sakthivel Srinivasan, Ravindran Rajan , Sheeladevi Rathinasamy (Journal of Applied Pharmaceutical Science, 2015)
Free radical scavenging activity was observed in both the methanol extract (M.E) and aqueous extract (A.E) of Scoparia dulcis respectively. In this study significant free radical scavenging activity was determined by evaluating the inhibition concentration (IC50) in each test. In 2, 2-diphenyl-1-picrylhydrazyl (DPPH) model the extract displayed potential free radicals scavenging activity with IC50 of M.E is 311.13µg/mL and A.E is 441.96μg/mL. Nitric oxide model displayed IC50 of 293.77µg/mL in M.E and 434.93µg/mL in A.E. While superoxide ion model showed IC50 of 281.02 µg/mL and 440.14µg/mL respectively for both methanol and aqueous extract when compared to standard ascorbic acid. The presence of phenol, flavonoid and total antioxidant in both the extract justifies the antioxidant potential of the plant which brings about its free radicals scavenging potential. GC-MS analysis showed the presence of 6 different phytochemicals with (Z)-7-Hexadecenyl acetate found to be the compound with maximum peak percentage 51.51% in M.E and β-Cyclocitral with 43.90% in A.E respectively. Thus we conclude that the antioxidant activities may be due to the cumulative effect of the phytochemicals present in the plant which genuinely designate them as free radical scavenger.
Keywords: Scoparia dulcis, antioxidant, free radicals, phytochemical, Gas chromatography–mass spectrometry (GC-MS).